PENGARUH CITRA MEREK, EKUITAS MEREK, KEPERCAYAAN MEREK, DAN PERILAKU MAHASISWA TERHADAP KEPUTUSAN MEMILIH KULIAH DI UNIVERSITAS NEGERI MALANG - Hidayat, Rachmad; Sulistyadi, Kohar; Purwaningsih, Yunastiti (Jurnal Pendidikan Insan Mandiri, 2016)
The purpose of this study is to determine: 1) the effect of the brand image, brand equity, and brand trust against the decision of selecting the State University of Malang, 2) find the solution in resolving problems arising from the brand image, brand equity, and brand trust the State University of Malang.This study is explanation research. The study population was a student University of Malang academic year of 2014. The research sample number of 170 students and is taken by using Proportionate Random Sampling technique. Data collection through questionnaires and documentation. The data analysis technique used is descriptive statistics and Structural Equation Modeling (SEM).Research results show that: 1) brand image and brand trust does not significant affect positively on student's decision in choosing the State University of Malang, while brand equity and significant positive effect on student's decision selecting State University of Malang, brand image, brand equity, and brand trust simultaneously have the effect of 45% of the student's decision in choosing the State University of Malang. Some solutions to strengthen the image of the State University of Malang, among others: a) conduct a more vigorous promotion again in the schools at the senior high school and vocational school, b) the alumni there are already successful or able to show themselves as alumni of State University of Malang, c) lecturers should be able to show his work, d) all of the institutional component should have a high productivity, e) manage and improve the network of information technology better, f) public leadership needs to be improved, and g) the name of the State University of Malang indeed need to be changed to make it more marketable. Keyword: brand image, brand equity, brand trust, student behavior, student decision